Penebusan Hanya Oleh Darah Anak Domba Allah (Yesus Kristus) 1 Perus 1:18-19 - Yoram H. A Tuan; Abad Jaya Zega (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
God created the first humans, namely Adam and Eve, both were created in the image and likeness of God and there was no sin in them, but Adam and Eve ultimately fell into sin because of human greed and violating what God commanded. They ate the fruit from the tree of the knowledge of good and evil which God had forbidden them to eat. Because when they eat it they die and death is what makes humans sin and lose the glory of God from themselves. In the book of Romans 3:23, it says "Sin separates humans from God and humans cannot come to God because of the conflict that occurs between humans and God. So sin leads humans to eternal death and destruction. But because God's love is so great for His special creation, namely humans, who are in the image and likeness of Him, that He took the initiative to free humans from the destruction caused by human sin itself.